Common variants in the chromosome 2p23 region containing the SLC30A3 (ZnT3) gene are associated with schizophrenia in female but not male individuals in a large collection of European samples. (30th December 2016) - Perez-Becerril, C.; Morris, A.G.; Mortimer, A.; McKenna, P.J.; de Belleroche, J.
Abstract: Previously, we found a significant gender-specific association of schizophrenia, in a UK case/control study, with SLC30A3, a candidate that is consistently down-regulated in schizophrenia in two independent cohorts. In view of the potential significance of this finding, we extended this study to a larger cohort using GWAS data from the Psychiatric Genetic Consortium (PGC). Meta-analysis was performed for the only two SLC30A3 SNP variants (rs11126936 and rs11126929) available in most PGC cohorts. A significant association with schizophrenia was found for both variants. When meta-analysis was performed in male and female case-control subsets, an increased and gender-specific effect of allele on risk of disease was found in females for both SNPs with no significant effect in males, which was further associated with a gender-specific effect on gene expression. In conclusion, using a large European-wide sample we were able to replicate the gender-specific association previously found in a UK cohort. Highlights: A gender-specific association between SLC30A3 and schizophrenia validation study was carried out. SLC30A3 encodes a zinc transporter (ZnT3) selective for glutamate synapses in CNS. SLC30A3 mRNA is significantly depleted in schizophrenia frontal cortex. This meta-analysis confirms the original findings. SLC30A3 may contribute to underlying differences in course, prognosis and treatment between males and females.